The Role of E-mail Communications in Determining Response Rates and Mode of Participation in a Mixed-mode Design. Issue 1 (February 2018) - Cernat, Alexandru; Lynn, Peter
This article is concerned with the extent to which the propensity to participate in a web face-to-face sequential mixed-mode survey is influenced by the ability to communicate with sample members by e-mail in addition to mail. Researchers may be able to collect e-mail addresses for sample members and to use them subsequently to send survey invitations and reminders. However, there is little evidence regarding the value of doing so. This makes it difficult to decide what efforts should be made to collect such information and how to subsequently use it efficiently. Using evidence from a randomized experiment within a large mixed-mode national survey, we find that using a respondent-supplied e-mail address to send additional survey invites and reminders does not affect survey response rate but is associated with an increased proportion of responses by web rather than face-to-face and, hence, lower survey costs.